PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF SISWA SMK MUHAMMADIYAH PURWOREJO - Vitrotul Amalia Khusna; Anita Rinawati; Lukman Fadhilliya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted with the aim of analyzing the nfluence of financial literacy and lifestyle on the consumptive behavior of students at SMK Muhammadiyah Purworej. The sampling technique used was proportionate stratified random sampling. Data were collected through questionnaires. This research is quantitative in nature, with multiple regression analysis as the data analysis method. The results of the study show that: (1) Based on descriptive analysis, respondent’s financial literacy is relatively high, with a percentage of 53%, while lifestyle and consumptive behavior fall into the less favorable category with percentages of 57% and 64%, respectively. (2) Financial literacy has a significant negative effect on the consumptive behavior of SMK Muhammadiyah Purworejo students, as indicated by a t-value of -2.874 < t-table (1.987) and a significance value of 0.005 < 0.05. (3) Lifestyle has a significant positive effect on the consumptive behavior of SMK Muhammadiyah Purworejo students, as shown by a t-value of 6.798 > t-table (1.987) and a significance value of 0.000 < 0.05. (4) There is a simultaneous influence of financial literacy and lifestyle on the consumptive behavior of SMK Muhammadiyah Purworejo students. The coefficient of determination (R²) is 0.301, meaning that 30.1% of the variation in consumptive behavior is explained by these two variables, while the remaining 69.9% is influenced by other factors beyond the scope of this study.